MINAT SISWA KELAS V DALAM MENGIKUTI PEMBELAJARAN BOLA KASTI DI SD NEGERI 58 BANDA ACEH - Mukti Darma; Helminsyah; Irwandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of students' interest in learning rounders (kasti) among fifth-grade students at SD Negeri 58 Banda Aceh. Interest is an important factor influencing the success of the learning process, especially in Physical Education, Sports, and Health (PJOK). This research employed a quantitative approach with a descriptive method. The population consisted of all fifth-grade students at SD Negeri 58 Banda Aceh with total sampling technique. The research instrument was a questionnaire developed based on indicators of interest, including enjoyment, attraction, attention, and student involvement. Data were analyzed using percentage and Mann-Whitney U test. The results showed that the level of students' interest in learning rounders was categorized as good (mean score = 53.79). Male students had higher interest (78.54%, high category) compared to female students (53.66%, medium category). The Mann-Whitney U test results showed a significant difference between male and female students' interest (U = 31.000, Z = -3.764, p = 0.000). Internal factors such as motivation and enjoyment, as well as external factors such as teaching methods and the learning environment, significantly influence students' interest. Therefore, teachers need to implement more varied and inclusive teaching methods to improve students' interest, particularly among female students.